NATRIUM SILIKAT SEBAGAI BAHAN PENGHAMBAT API AMAN LINGKUNGAN - Achmad Hidajat Effendi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
This research aims at investigating the effectiveness of fire retardant siliceous based materials which is made of natrium silicate (Na2SiO3.2H2O). Factors related to selection of mixed composition with respect to fire such as the easiness in processing or coating as well as the optimum weight of coating per m2 are investigated. Experimental method is used in this research with equipment used in this experiment include Fire Propagation Test Apparatus (based on JIS A 1321, 1994, # 605). Experiment is done on Borneo and Red Meranti Wood and comparison is done on the result of test undertaken on these types of wood which are treated with siliceous based fire retardant materials. Investigation also reveals that the more natrium silicate absorbed by the wood will increase the temperature rise (td è) and smoke developed index. Experiment on mixture composition of 1 : 1 on both woods has proven it. The best mixture of siliceous based fire retardant against fire while ensuring ease workmanship is under the ratio 7 : 1 up to 10 : 1, with the layer optimum weight per m2 is approximately 0.7 kg. Using this type of fire retardant has proven the increase in the quality ofBorneo wood and Red Meranti wood from quality class 4 (Semi fire retardant) to become quality class 2 (Semi non combustible).